2015
DOI: 10.1021/acs.est.5b02251
|View full text |Cite
|
Sign up to set email alerts
|

Desulfovibrio vulgaris Growth Coupled to Formate-Driven H2 Production

Abstract: Formate is recognized as a superior substrate for biological H2 production by several bacteria. However, the growth of a single organism coupled to this energetic pathway has not been shown in mesophilic conditions. In the present study, a bioreactor with gas sparging was used, where we observed for the first time that H2 production from formate can be coupled with growth of the model sulfate-reducing bacterium Desulfovibrio vulgaris in the absence of sulfate or a syntrophic partner. In these conditions, D. vu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…Research with D. vulgaris indicated that intracellular cycling of formate formed by pyruvate formate lyase might contribute to energy conservation 48 . Formate conversion to hydrogen and carbon dioxide indeed is coupled to energy conservation and growth of Desulfovibrio , even in the absence of sulfate 49 , 50 . Interestingly, the presumed formate dehydrogenase complex of D. kuznetsovii does not have much similarity with any of the formate dehydrogenases of D. vulgaris .…”
Section: Resultsmentioning
confidence: 99%
“…Research with D. vulgaris indicated that intracellular cycling of formate formed by pyruvate formate lyase might contribute to energy conservation 48 . Formate conversion to hydrogen and carbon dioxide indeed is coupled to energy conservation and growth of Desulfovibrio , even in the absence of sulfate 49 , 50 . Interestingly, the presumed formate dehydrogenase complex of D. kuznetsovii does not have much similarity with any of the formate dehydrogenases of D. vulgaris .…”
Section: Resultsmentioning
confidence: 99%
“…The aforementioned findings demonstrate the occurrence and potential activity of FHL‐containing taxa in the root‐zone, many of which are likely facultative aerobes as illustrated by the detection of a large number of hydrogenase genes that are probably derived from facultative aerobes and also by the isolation of FHL‐containing SB1 and SB2, both of which are facultative aerobes. However, it should be noted that obligate anaerobes such as sulfate reducers and methanogens may form H 2 from formate independent of FHL by the combined activities of formate dehydrogenase and different hydrogenases (e.g., in the case of methanogens, by H 2 ‐forming methylenetetrahydromethanopterin dehydrogenase) (Wu et al, ; Lupa et al, ; Martins and Pereira, ; Martins et al, ). Thus, H 2 might also be produced from formate independent of FHL.…”
Section: Discussionmentioning
confidence: 99%
“…Cultures were either grown under anaerobic conditions or under continuous O 2 -sparging conditions with a gas flow rate of 40 ml min −1 at various oxygen concentrations provided by a gas mixer (PEGAS 4000 MF, Columbus Instruments, USA) as previously described (Ramel et al, 2015). Growth in pyruvate/sulfate-free medium was performed either under anaerobic conditions or under continuous N 2 sparging (40 ml min −1 ) to lower the hydrogen partial pressure in the culture (Martins et al, 2015). The absence of contamination in the cultures were regularly checked by wet mount microscopy as well as by streaking culture aliquots onto a Luria-Bertani agar plate followed by an incubation at 37 C. The dissolved oxygen concentration was monitored using a Mettler-Toledo M700 recorder equipped with an O 2 module ppb 4700 and a calibrated Inpro 6900 O 2 probe.…”
Section: Bacterial Growth Conditionsmentioning
confidence: 99%